2015
DOI: 10.1007/s11595-015-1178-6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of layered double hydroxides on ultraviolet aging resistance of SBS modified bitumen membrane

Abstract: Layered double hydroxides (LDHs)/styrene-butadiene-styrene (SBS) copolymer modified bitumen was prepared by melt blending. The effect of LDHs on the ultraviolet (UV) aging behavior of SBS modifi ed bitumen was investigated. The changes of chemical structures of modifi ed bitumen before and after UV aging were characterized by Fourier transform infrared spectroscopy (FTIR). The results show that LDHs obviously reduce the variation of softening point and low temperature fl exibility of SBS modifi ed bitumen unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…Pristine bitumen was poured into an oil-bath heating iron container, and heated to a well fluid at around 140°C. The weighed LDHs or OLDHs (3 wt.% by weight of bitumen as determined by our previous study [28]) were added into the bitumen, and then, the blend was sheared for an hour at the shearing temperature of (140 ± 5)°C and shearing rate of 4000 rpm to ensure fully homogenous. Finally, the modified bitumen was poured into molds to conduct related experiments and tests.…”
Section: Preparation Of Modified Bitumenmentioning
confidence: 99%
“…Pristine bitumen was poured into an oil-bath heating iron container, and heated to a well fluid at around 140°C. The weighed LDHs or OLDHs (3 wt.% by weight of bitumen as determined by our previous study [28]) were added into the bitumen, and then, the blend was sheared for an hour at the shearing temperature of (140 ± 5)°C and shearing rate of 4000 rpm to ensure fully homogenous. Finally, the modified bitumen was poured into molds to conduct related experiments and tests.…”
Section: Preparation Of Modified Bitumenmentioning
confidence: 99%
“…Several works have studied the impact of these environmental conditions on the degradation and accelerated aging processes of the BS. However, these works have focused on the physical and mechanical properties of the BS [39][40][41][42], ignoring the environmental aspects that these degradation processes may have, such as the emission of pollutants to the environment. Since the main purpose of BS is to physically seal the roof surfaces, it is well understood why the physical properties of the sheets are so important and well-studied.…”
Section: Bitumen Sheets and Water Qualitymentioning
confidence: 99%
“…As aforementioned, sun radiation is assumed to have an important role in the degradation processes of the BS [40,41,46], which may affect the release of different components to the roof water. Therefore, the 'Sun' and 'Shade' setups were examined under the conditions of exposure to direct and indirect sun radiation, which were measured throughout the period of the study at a meteorological station of the Israeli Meteorological Service, located ~1 km north of roof #3, where the experiment was conducted (data available on line https://ims.data.gov.il/he/ims/6 (accessed on 13 September 2021)).…”
Section: Controlled Experimental Studymentioning
confidence: 99%
“…Wu et al [ 20 ] proved that LDHs can alleviate the damaging effects of UV light on the rheological properties, and strengthen the anti-UV aging properties of bitumen. Xu et al [ 21 ] found that LDHs can reduce bitumen aging and reduce SBS degradation. However, as an inorganic material, the strong hydrophilicity of LDHs can result in poor storage stability in bitumen [ 22 ].…”
Section: Introductionmentioning
confidence: 99%